IDIOMATIC EXPRESSION FOUND IN AVRIL LAVIGNEâS SONG LYRICS ALBUM LET GO 2002 - Daulay, Tiany; Rasyidah, Ummi; Antoni, Rivi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research is to find out and explain idiom that there in avril lavigneâs song lyrics in album let go 2002. This research is about descriptive qualitative, in which has purpose to make description about idiom that there in avril lavigne song lyrics. This research was done with steps in collecting the data that is by accessing to the internet, searching the song lyrics, reading and finding the idiom. Then, the data was taken with using mcgraw-hills dictionary, oxford dictionary of idioms and make the conclusion. Thus, can be concluded that there are 56 idioms was found and most of them have contextual.